Species composition and DNA barcoding of hemipteran assemblages throughout paddy growing seasons - Yaakop, Salmah; Sabri, Suliza; Kamaruddin, Nur ‘Aimi Kamalia; Norizam, Norlaila Nabila; Mohammed, Muhamad Azmi (Universiti Putra Malaysia Press, 2022)
Hemipterans are the diverse, abundant, and important pests in the paddy ecosystem due to their piercing and sucking mouthparts that feed on the crop causing significant losses in rice yields. Despite their important roles in the paddy ecosystem, the information on DNA barcode, diversity, and species richness has been occasionally discussed. This study aimed to measure its abundance, species richness, and barcode hemipteran species from the paddy ecosystem. Active sampling was used with two different sampling arrangements in the paddy ecosystem in Sabak Bernam, Selangor, for two different seasons. Hemipterans were collected and identified up to species level morphologically prior to DNA barcoding. The richness and the abundance of species were measured along with the paddy growth phases (vegetative, reproductive, and mature). A total of 2,167 individuals of seven hemipteran species (Cyrtorhinus lividipennis, Leptocorisa oratorius, Nephotettix virescens, Cofana spectra, Sogatella furcifera, Scotinophara coarctata, and Graptostethus sp.) were successfully collected with Shannon-Diversity Index (H’ = 0.4572), Margalef richness index (D = 0.7811), and Evenness Index (E = 0.2257). There was no significant difference (p > 0.05) for species diversity in both seasons. The highest abundance of hemipteran was during the maturity stage (1,543 individuals), followed by the reproductive (591 individuals) and vegetative stages (33 individuals). This study observed a significant difference between the paddy growth for both seasons (p < 0.05). Five hemipteran species namely C. lividipennis, L. oratorius, N. virescens, C. spectra, and S. furcifera, were successfully barcoded with Leptocorisa, the dominant genus. Outcomes from this study suggested that different hemipteran management approaches must be developed to cater to different hemipteran species at different paddy growth stages for a successful and sustainable paddy growing practice in Malaysia.